Original paperTandem-ring dwell time ratio in Nigeria: dose comparisons of two loading patterns in standard high-dose-rate brachytherapy planning for cervical cancer - Ibhade, Obed Rachel; Oyeyemi, Oyekunle Emmanuel; Idayat, Akinlade Bidemi; Atara I., Ntekim (Journal of Contemporary Brachytherapy, 2015)
Purpose : In high-dose-rate (HDR) brachytherapy (BT), the source dwell times and dwell positions are essential treatment planning parameters. An optimal choice of these factors is fundamental to obtain the desired target coverage with the lowest achievable dose to the organs at risk (OARs). This study evaluates relevant dose parameters in cervix brachytherapy in order to assess existing tandem-ring dwell time ratio used at the first HDR BT center in Nigeria, and compare it with an alternative source loading pattern. Material and methods : At the Radiotherapy Department, University College Hospital (UCH), Ibadan, Nigeria, a total of 370 standard treatment plans in two alternative sets were generated with HDR basic 2.6 software for one hundred and eighty five cervical cancer patients. The initial 185 individual plans were created for clinical treatment using the tandem-ring dwell time ratio of 1 : 1. Modifying the initial applicator loading ratio, the second set of plans with related dose data were also obtained for study purposes only. Total reference air kerma (TRAK), total time index (TTI), ICRU volume, treatment time, point B dose, ICRU bladder dose, and rectal points dose were evaluated for both sets of plans. Results : The means of all evaluated dose parameters decreased when the existing tandem-ring dwell time ratio (1 : 1) was modified to other dwell weightings (1 : 1 – 3 : 1). These reductions were 13.43% (ICRU volume), 9.83% (rectal dose), 6.68% (point B dose), 6.08% (treatment time), 5.90% (TRAK), 5.88% (TTI), and 1.08% (bladder dose). Correspondingly, coefficients of variation changed by –7.98%, –5.02%, –5.23%, –4.20%, –3.93%, 8.65%, and 3.96% from the existing pattern to the alternative one. Conclusion : Tandem-ring dwell time ratio has significant influence on dosimetric parameters. This study has indicated the need to modify the existing planning approach at UCH.